Search for a W′ boson decaying to a τ lepton and a neutrino in proton-proton collisions at √s = 13 TeV - Sirunyan, A. M. (2019)
A search for a new high-mass resonance decaying to a τlepton and a neutrino is reported. The analysis uses proton-proton collision data collected by the CMS experiment at the LHC at √s=13 TeV, corresponding to an integrated luminosity of 35.9fb−1. The search utilizes hadronically decaying τleptons. No excess in the event yield is observed at high transverse masses of the τand missing transverse momentum. An interpretation of results within the sequential standard model excludes W boson masses below 4.0TeVat 95% confidence level. Existing limits are also improved on models in which the W boson decays preferentially to fermions of the third generation. Heavy W bosons with masses less than 1.7–3.9TeV, depending on the coupling in the non-universal G(221) model, are excluded at 95% confidence level. These are the most stringent limits on this model to date.